Simplified Building design for wind and earthquake forces - Ambrose, James (Wiley, 1980)
Dynamic effects on building structures - Lateral load resistance of buildings - Wind effects on buildings - Earthquake effects on buildings - Elements of lateral load resistive systems - Analysis and design for wind - Analysis and design for earthquake forces - Special problems.